A Computerized Repository System for Collection and Retrieval of Acceleration Stress Research Data - Whinnery, J. E.; Slaughter, J. W. (Methods of Information in Medicine, 1981)
A data repository system for use in aeromedical acceleration research has been developed and is currently in use at the USAF School of Aerospace Medicine. The major functions of the repository include: a) increasing safety in human acceleration experimentation, b) documentation of clinical aeromedical evaluations, c) interface with management utilization systems, and d) rapid retrieval of data for analysis to enable a more in-depth understanding of +Gz physiology. The repository utilizes the System 2000 Data Base Management System. The applications of the data base are illustrated by several examples including the electrocardiographic response to acceleration stress.
Keywords: +GZ Stress; Aeromedical Research; Information Processing; Database Design